? Analysis of Crutches System to Select and Guide the Design of Crutches Suitable for Different Sizes of Siege Timber and Development of Tree Crutches - Napassara Lattikapong, Onvalee Amornleetrakul, Sippawich Kambung (Mathematical Statistician and Engineering Applications, 2022)
Root system is the most important of trees for absorb nutrients and were anchorage to growth tree. But when the urban trees were transplanting, they always moved out the taproot affect to reduces tree anchorage. In some cases, severe wind loads can trigger uprooting affects the life and property of users. Therefore, the urban trees must be supported by crutches. However, about designing the crutches some users never know about how to install and usability as well as the duration of use. The results of this research show the difference in suitability for use of three varies tree crutches are the pavilion tree crutches, the implant crutches, and wire rope anchors. By calculating the size of the tree and bracing, the gravity of the tree, process and complexity of work, and sustainability of materials. In order that users can understand and apply and control the installation for various tree sizing to the design of their own landscape area.